Variability of Semantic Structure of Oral Spontaneous Monologues “About Myself” depending on “Gender” Factor - D. S. Pavlova; M. V. Garanovich (Научный диалог)
The influence of the social factor “gender of speakers” on the semantic structure of spontaneous monological texts generated by them is considered. A review of sociolinguistic studies on the influence of this social factor on the processes of text formation is made. The conclusion is made about the expediency of applying the methods of sociolinguistics and cognitive linguistics in the study of the problem of gender conditionality of the generation of oral spontaneous texts. The authors highlight the existing linguistics views on the text and its structure. A new understanding of semantic structure of a text is proposed as a set of semantic components of a text at different levels (micro-topics of a text and lexical units, semantics of which implements these micro-topics), and the hierarchical system of various relations (semantic and grammatical) between lexical units and micro-topics forming a unity deep and surface structures of the text. The author’s method of semantic analysis of the linked text fields is used, based on the method of graphosemantic modelling implemented in the IS “Semograph.” The material of the study was 48 oral spontaneous monologues “About myself,” the sample is balanced in terms of “gender,” “age” and “education.” Particular attention is paid to the analysis of the influence of the factor “gender” on the variability of the semantic structure of the oral spontaneous monologues “About myself,” which interacts with other social parameters of speakers (age and education).